2014
DOI: 10.3906/sag-1211-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological effects of methanolic extracts of Rubus fruticosus L.

Abstract: Leguminous crops suffer severely in soils poor in phosphorus. A 2-factor factorial experiment was conducted in a net-house to explore the effect of graded levels of P fertilizer (0, 30, and 60 kg P ha -1 or P 0 , P 30 , and P 60 , respectively) together with rhizobium (biological nitrogen fertilizer (BNF)) and/or phosphate-solubilizing bacteria (biological phosphorus fertilizer (BPF)) in terms of nutrient uptake, yield, and quality of chickpea (Cicer arietinum L.). Phosphorus was applied as basal dose, while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…According to the Riaz et al, shortening of immobility period indicates antidepressant, and prolongation of this period symbolizes the CNS depression-like effect in FST and TST [25]. In both experiments, D. malabarica extract significantly decreased the immobility time which indicates the possession of antidepressant active constituents in extract.…”
Section: Discussionmentioning
confidence: 70%
“…According to the Riaz et al, shortening of immobility period indicates antidepressant, and prolongation of this period symbolizes the CNS depression-like effect in FST and TST [25]. In both experiments, D. malabarica extract significantly decreased the immobility time which indicates the possession of antidepressant active constituents in extract.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, this berry fruit has been evaluated in different concentrations and behavioral tests such as the EPM and the social interaction test [102]. Likewise, a methanolic extract of blackberry (Rubus fruticosus) was used and reported an anxiolytic effect (100,200, and 300 mg/kg, orally) in the hole-board test in a dose-dependent response [108]; also, the effect of Rubus brasiliensis fruits in Wistar rats has been studied, reporting an anxiolytic effect in EPM, in a dose of 2.5 mg/kg administered per gavage [109]. In turn, an anxiety-related effect has been reported in treated male Swiss mice through supplemented water (2.6-3.2 mg/kg) per day of anthocyanins present in blueberry (Vaccinium ashei) [19].…”
Section: Anxietymentioning
confidence: 99%
“…Several anxiolytic, muscle relaxant and sedativehypnotic drugs exhibit their action via GABA. Thus it may be assumed that the leaf and stem bark extracts of W. chinensis may act by potentiating GABAergic inhibition in the CNS via membrane hyperpolarization that lead to a reduction in the firing rate of critical neurons in the brain or the extracts may simply activate the GABA receptors directly (Riaz et al, 2014). Again, research has shown that plants containing flavonoids, saponins and tannins are useful for the treatment of many CNS disorders as they reduce the locomotor activity of the CNS (Azanchi et al, 2014).…”
Section: Cns Depressant Activity By Open Field Testmentioning
confidence: 99%